Simulation of the FDA nozzle benchmark: A lattice Boltzmann study. (June 2022) - Huang, Feng; Noël, Romain; Berg, Philipp; Hosseini, Seyed Ali
Highlights: Simulation of FDA nozzle geometry with in-house lattice Boltzmann solver. Simulation of laminar, transitional and turbulent regime flows. Validation against experimental data from PIV measurements. Study of under-resolved simulations data quality. Abstract: Background and objective: Contrary to flows in small intracranial vessels, many blood flow configurations such as those found in aortic vessels and aneurysms involve larger Reynolds numbers and, therefore, transitional or turbulent conditions. Dealing with such systems require both robust and efficient numerical methods. Methods: We assess here the performance of a lattice Boltzmann solver with full Hermite expansion of the equilibrium and central Hermite moments collision operator at higher Reynolds numbers, especially for under-resolved simulations. To that end the food and drug administration's benchmark nozzle is considered at three different Reynolds numbers covering all regimes: (1) laminar at a Reynolds number of 500, (2) transitional at a Reynolds number of 3500, and (3) low-level turbulence at a Reynolds number of 6500. Results: The lattice Boltzmann results are compared with previously published inter-laboratory experimental data obtained by particle image velocimetry. Our results show good agreement with the experimental measurements throughout the nozzle, demonstrating the good performance of the solver even in under-resolved simulations. Conclusion: In this manner, fast but sufficiently accurate numerical predictions can be achieved for flow configurations of practical interest regarding medical applications.